Doulas and intimate labour;boundaries, bodies, and birth. (DEMETER Press, 2015)
Scholars turn to reproduction for its ability to illuminate the practices involved with negotiating personhood for the unborn, the newborn, and the already-existing family members, community members, and the nation. The scholarship in this volume draws attention to doula work as intimate and relational while highlighting the way boundaries are created, maintained, challenged, and transformed. Intimate labour as a theoretical construct provides a way to think about the kind of care doulas offer women across the reproductive spectrum. Doulas negotiate boundaries and often blur the divisions betw.